Phoenixin-14 alleviates inflammatory smooth muscle cell-induced endothelial cell dysfunction in vitro. (September 2022) - Ling, Cong; Yang, Yang; Hu, Xiling; Cai, Meiqin; Wang, Hui; Chen, Chuan
Abstract: Background: Intracranial aneurysm (IA) is cerebrovascular disorder which refers to local vessel wall damage to intracranial arteries, forming abnormal bulge. Both endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) are closely associated with IA formation and rupture. Inflammatory SMCs (iSMCs) were reported to induce EC dysfunction and result in IA progression. Phoenixin-14 (PNX-14) is a recently discovered brain peptide with pleiotropic roles, which participates in reproduction, cardio protection, lipid deposition and blood glucose metabolism. PNX-14 was previously reported to protect brain endothelial cells against oxygen-glucose deprivation/reoxygenation (OGD/R)-induced cell injury. Therefore, our study was designed to investigate the influence of PNX-14 on iSMCs-induced endothelial dysfunction. Methods: Inflammation in SMCs was induced by cyclic mechanical stretch. Human umbilical vein endothelial cells (HUVECs) were exposed to SMC- or iSMC-conditioned medium and then treated with 100 nM PNX-14 for 24 h. The levels of proinflammatory cytokines (IL-1β, IL-6 and TNF-α) in cell supernatants were analyzed by ELISA. Cell viability, apoptosis, angiogenesis and migration were subjected to CCK-8 assay, flow cytometry analysis, tube formation assay and Transwell migration assay. The protein levels of proinflammatory cytokines and apoptosis markers (Bcl-2 and Bax) were evaluated by western blotting. Results: Cyclic mechanical stretch upregulated IL-1β, IL-6 and TNF-α levels in SMCs. Treatment with SMC- or iSMC-conditioned medium HUVECs inhibited cell viability, angiogenesis and migration and induced apoptosis in HUVECs. iSMC-conditioned medium has more significant effects on cell functions. However, the influence of SMC- or iSMC-conditioned medium treatment on HUVEC biological functions were reversed by PNX-14 treatment. PNX-14 exerts no significant influence on the biological functions of HUVECs treated with SMC medium. Conclusion: PNX-14 alleviates iSMCs-induced endothelial cell dysfunction in vitro.